Pengaruh Literasi Keuangan Motivasi Kerja Penggunaan Media Sosial Terhadap Keberlangsungan Bisnis UMKM di Kecamatan Sandubaya Kota Mataram - Muhammad Mahyudin Muhtar; Noor Shodiq Askandar; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of financial literacy, work motivation, and the use of social media on the sustainability of MSME business in Sandubaya District, Mataram City. The independent variables in this study are financial literacy, work motivation, and use of social media, while the dependent variable is the business continuity of MSMEs in Sandubaya District, Mataram City. This type of research is quantitative research. The source of data in this study is primary data with data collection methods in the form of a questionnaire. The population in this study were SMEs in the Sandubaya District, Mataram City, with a sample of 98 people. By using regression analysis, it is found that the financial literacy and work motivation variables have no effect on the sustainability of the MSME business, while the social media use variable has a positive and significant effect on the MSME business continuity. These results imply that increasing and socializing the use of social media is needed to increase income. Entrepreneurship through social media is used for promotional tools and other social media users will begin to recognize and know what is offered.Keywords: Financial literacy, work motivation, use of social media. MSME business continuity.